Long-Term Follow-up of Complex Calcaneal Osteomyelitis Treated With Modified Gaenslen Approach. Issue 4 (October 2022) - Kendal, Adrian; Loizou, Constantinos; Down, Billy; McNally, Martin
Background: The treatment of chronic calcaneal osteomyelitis is a challenging and increasing problem because of the high prevalence of diabetes mellitus and operative fixation of heel fractures. In 1931, Gaenslen reported treatment of hematogenous calcaneal osteomyelitis by surgical excision through a midline, sagittal plantar incision. We have refined this approach to allow successful healing and early mobilization in a modern series of complex patients with hematogenous, diabetic, and postsurgical osteomyelitis. Methods: Twenty-eight patients (mean age 54.6 years, range 20-94) with Cierny-Mader stage IIIB chronic calcaneal osteomyelitis were treated with sagittal incision and calcaneal osteotomy, excision of infected bone, and wound closure. All patients received antibiotics for at least 6 weeks, and bone defects were filled with an antibiotic carrier in 20 patients. Patients were followed for a mean of 31 months (SD 25.4). Primary outcome measures were recurrence of calcaneal osteomyelitis and below-knee amputation. Secondary outcome measures included 30-day postoperative mortality and complications, duration of postoperative inpatient stay, footwear adaptions, mobility, and use of walking aids. Results: All 28 patients had failed previous medical and surgical treatment. Eighteen patients (64%) had significant comorbidities. The commonest causes of infection were diabetes ± ulceration (11 patients), fracture-related infection (4 patients), pressure ulceration, hematogenous spread, and penetrating soft tissue trauma. The overall recurrence rate of calcaneal osteomyelitis was 18% (5 patients) over the follow-up period, of which 2 patients (7%) required a below-knee amputation. Eighteen patients (64%) had a foot that comfortably fitted into a normal shoe with a custom insole. A further 6 patients (21%) required a custom-made shoe, and only 3 patients required a custom-made boot. Conclusion: Our results show that a repurposed Gaenslen calcanectomy is simple, safe, and effective in treating this difficult condition in a patient group with significant local and systemic comorbidities. Level of Evidence: Level IV, retrospective case series.